Video analytics : face and facial expression recognition and audience measurement : third International Workshop, VAAM 2016, and second International Workshop, FFER 2016, Cancun, Mexico, December 4, 2016, Revised selected papers /: face and facial expression recognition and audience measurement : third International Workshop, VAAM 2016, and second International Workshop, FFER 2016, Cancun, Mexico, December 4, 2016, Revised selected papers. (2017) - Unknown
No abstract available